Literature Review: The Long-Term Use Effect of Proton Pump Inhibitors and The Risk of Fractures - Fatharani, Adelia; Hilmi, Indah Laily (Sean Institute, 2022)
Proton Pump Inhibitors (PPIs) are a group of drugs widely used to treat gastrointestinal disorders. Long-term use of PPIs has a risk of several side effects, one of them is fractures. The aims of this study is to examine the relationship between long-term PPIs use and the risk of fractures. The method in this literature review was literature study by searching for research article through Google Scholar and Pubmed Central by using the keywords